Towards the Development of Czech Word (En)clitics - Kosek, Pavel (Bohemica Olomucensia, 2016)
The paper deals with fundamental developmental trends of word order of Czech word enclitics (as distinct from sentence enclitics). The Czech word enclitics are: short forms of two-syllabic pronouns (mi, si, ti, ho, mu, tě, se) and forms of conditional and praeterital auxiliary verbs. The paper summarizes what has been up to now written about the development of enclitics in comprehensive works dealing with Czech historical grammar and proposes principles of future research of their development. The word order of Czech word enclitics can be seen as a competition of three positions: a) Postinitial position, which may be realized either as the 2W position or the 2D position. b) Contact position of clitics adjacent to an item with which the clitic is syntactically associated; contact word order can be found in medial, prefinal and final clausal positions. c) Non-contact (isolated) position of clitics placed in clause-medial position, non-adjacent to the item on which the clitic is dependent or with which it combines to create an analytical form; the clitic is placed after the first stressed element in the colon (metrical sequence), i.e., its position is governed by prosodic rules that are analogous to those rules influencing its postinitial position. This position is seldom found, it is used as a means of emphasis within functional sentence perspective.
Keywords: word order; Czech word enclitics; Czech historical grammar